University Library Data Analysis to Help Book Collection Procurements using C4.5 Algorithm (Case Study: Udayana University Postgraduate Library) - Oka Kessawa Adnyana, Anak Agung Gede; Darma Kotama, I Nyoman; Sudarmojo, Yanu Prapto (International Journal of Engineering and Emerging Technology; Vol 4 No 1 (2019): January - June, 2019)
Library is one of many requirements for a university to be labeled as qualified university. Udayana University’s Library collections is one major concern. To keep a good collections that can fulfill the student and other academic purposes fulfilled. To create an efficient procurement, we need to keep tracks on every transactions that happening, to determine whether it is important to procure certain books from a certain study field by going through number of lending, number of novelty and book counts. Using C4.5 to learn about past procurement we are going to create an effective procurement